Correlation between potassium administration and resolution in patients with diabetic ketoacidosis - Rina Oktaviani; Zullies Ikawati; Nanang Munif Yasin (Universitas Islam Indonesia, 2021)
Abstract Background: Diabetic ketoacidosis (DKA) is a life-threatening complication of acute diabetes mellitus (DM). Insulin is one of the therapies for DKA, which can reduce potassium levels by shifting potassium from extracellular to intracellular. Consequently, early administration of potassium is important in the resolution of DKA.Objective: To determine the correlation between potassium administration and resolution in patients with DKA and the factors affecting such resolution.Methods: An observational study was employed with a retrospective cohort design for inpatients with a diagnosis of DKA during the period of January 2015-August 2020 at Dr. Sardjito Hospital Yogyakarta. Appraisal of the resolution of DKA variable was based on the achievement of blood glucose targets, followed by 2 criteria of serum bicarbonate, pH, and anion gap during 24 hours of therapy. This study involved 55 patients divided into groups with potassium administration and without potassium administration. Data were analyzed using the chi-square test and multivariate logistic regression.Results: The resolution of DKA achieved in less than equal to 24 hours in the group with potassium was 48.5% (16 patients) while it was 18.2% (4 patients) without potassium. Based on the chi-square analysis, there was a relationship between potassium administration and the resolution of DKA (p=0.045; RR=2.667; 95%CI=1.028-6.920). The multivariate analysis showed that the severity and history of DM were positively related to the resolution of DKA (p=0.025; OR: 8.901; 95%CI=1.318-60.123 and p=0.017; OR: 0.090; 95%CI=0.012-0.652).Conclusion: Potassium administration resulted in 48.5% of the DKA patients achieving a resolution in less than equal to 24 hours from the commencement of DKA therapy. The severity and history of DM became the factors that affected the resolution of DKA.Keywords: diabetic ketoacidosis, potassium, resolution Intisari Latar belakang: Ketoasidosis diabetik (KAD) adalah komplikasi akut diabetes melitus (DM) yang mengancam jiwa. Insulin merupakan salah satu terapi KAD, yang dapat menurunkan kadar kalium dengan cara memindahkan kalium dari ekstraseluler ke intraseluler, sehingga pemberian awal terapi kalium berperan penting dalam resolusi KAD.Tujuan: Mengetahui hubungan pemberian kalium dengan resolusi pada pasien KAD dan faktor yang mempengaruhi resolusi.Metode: Penelitian observasional dengan rancangan kohort retrospektif pada pasien rawat inap dengan diagnosis KAD periode Januari 2015–Agustus 2020 di RSUP Dr. Sardjito Yogyakarta. Penilaian variabel resolusi KAD adalah ketercapaian target glukosa darah, diikuti 2 kriteria dari serum bikarbonat, pH, dan anion gap selama 24 jam terapi. Penelitian melibatkan 55 pasien yang terbagi ke dalam kelompok pemberian kalium dan tanpa pemberian kalium. Data dianalisis menggunakan uji chi-square dan multivariate logistic regression.Hasil: Resolusi KAD yang dicapai selama kurang dari sama dengan 24 jam pada kelompok dengan pemberian kalium sebesar 48,5% (16 pasien) dan 18,2% (4 pasien) tanpa pemberian kalium. Berdasarkan analisis chi-square, terdapat hubungan antara pemberian kalium dengan resolusi KAD (p=0,045; RR=2,667; 95%CI=1,028-6,920). Hasil analisis multivariat menunjukkan derajat keparahan dan riwayat DM berhubungan positif terhadap resolusi KAD (p=0,025; OR=8,901; 95%CI=1,318-60,123 dan p=0,017; OR=0,090; 95%CI=0,012-0,652).Kesimpulan: Pemberian kalium menghasilkan 48,5% pasien KAD yang mencapai resolusi kurang dari sama dengan 24 jam dari awal terapi KAD dimulai. Derajat keparahan dan riwayat DM merupakan faktor yang mempengaruhi resolusi KAD.Kata kunci: ketoasidosis diabetik, kalium, resolusi